HT‐NbOsB: Experimental and Theoretical Investigations of a Boride Structure Type Containing Boron Chains and Isolated Boron Atoms. Issue 28 (27th June 2018) - Forsythe, Ryland; Scheifers, Jan P.; Zhang, Yuemei; Fokwa, Boniface P. T.
Abstract: Invited for the cover of this issue is the group of Boniface Fokwa from the University of California, Riverside, USA. The cover image shows two boron fragments found in the modifications of NbOsB: a finite B4 fragment (left) and the infinite B‐chain (right) as typically found in borides with a smaller metal‐to‐boron ratio. Abstract : The biggest challenge is for sure the controlled synthesis of metal borides… Read more about the story behind the cover in the Cover Profile and about the research itself in theFull Paper by B. P. T. Fokwa et al.